Application of maqâṣid al-sharî’ah in murâbahah contract in sharia financial institutions - Amrulla Hayatudin; Panji Adam (Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Negeri (IAIN) Salatiga, 2020)
The development of the Islamic finance industry, especially Islamic banking, demands product innovation. Based on its business activities, Islamic banking implements three types of business activities, there are fundraising, distribution, and banking service activities. The Financing products that are widely used are Murâbahah contracts. The implementation of Murâbahah in Lembaga Keuangan Syariah (LKS) has been modified, so that the sharia signs and spirits are needed to remain in the sharia corridor. This type of research is library research with normative juridical methods. The results showed that Maqâṣid al-syarî'ah is an important component in Islamic financial institutions. Because, without the implementation of Maqâṣid al-syarî'ah in the development system of Islamic financial institutions, muamalah products are developed, banking and financial regulations will be rigid and static, consequently Islamic banking and financial institutions will be difficult to develop.